2023
DOI: 10.1002/adma.202305424
|View full text |Cite
|
Sign up to set email alerts
|

Regulating Phase Separation Kinetics for High‐Efficiency and Mechanically Robust All‐Polymer Solar Cells

Abstract: All‐polymer solar cells (all‐PSCs) possess excellent operation stability and mechanical robustness than other types of organic solar cells, thereby attracting considerable attention for wearable flexible electron devices. However, the power conversion efficiencies (PCEs) of all‐PSCs are still lagging behind those of small‐molecule‐acceptor‐based systems owing to the limitation of photoactive materials and unsatisfactory blend morphology. Herein, a novel terpolymer denoted as PBDB‐TFCl (poly4,8‐bis(5‐(2‐ethylhe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…The shorter τ 1 and τ 2 values indicate a faster diffusion rate of excitons toward the interface before dissociation and a more rapid exciton dissociation at the D/A interface. These findings illustrate that the treatment of DIO accelerates the hole transfer kinetics, boosting the photogenerated current and thereby enhancing the photovoltaic performance of the all-PSCs. , …”
Section: Resultsmentioning
confidence: 80%
“…The shorter τ 1 and τ 2 values indicate a faster diffusion rate of excitons toward the interface before dissociation and a more rapid exciton dissociation at the D/A interface. These findings illustrate that the treatment of DIO accelerates the hole transfer kinetics, boosting the photogenerated current and thereby enhancing the photovoltaic performance of the all-PSCs. , …”
Section: Resultsmentioning
confidence: 80%
“…To date, many halogenated polymer donors‐based all‐PSCs have achieved a PCE more than 17 % (Figure 1a). The halogenated polymer donors includes D18, [10] D18‐Cl, [11] PQM‐Cl, [12] PBQx‐TF, [13] PDBQx‐TCl, [14] PBBTz‐Cl, [15] PM6, [16] etc. These polymer donors possess deep‐lying HOMO energy level and strong molecular stacking, contributing to high PCEs.…”
Section: Introductionmentioning
confidence: 99%
“…All-polymer solar cells (APSCs), which utilize a physical blend of pand n-type polymers as the photoactive layer, are a subtype of organic PVs gaining traction for IPV applications, offering superior mechanical stability and morphological durability [9]. Although APSCs have been extensively researched in outdoor applications [10][11][12][13][14][15], their applications in indoor photovoltaic applications still lag. Although a few studies have demonstrated high V OC and PCE in APSCs tailored for IPV applications, these investigations show the potential of APSCs as efficient and durable IPV solutions [16].…”
Section: Introductionmentioning
confidence: 99%